Theology and the scientific imagination from the Middle Ages to the seventeenth century - Funkenstein, Amos (Princeton University Press, 2018)
Theology and the scientific imagination is a pioneering work of intellectual history that transformed our understanding of the relationship between Christian theology and the development of science. Distinguished scholar Amos Funkenstein explores the metaphysical foundations of modern science and shows how, by the 1600s, theological and scientific thinking had become almost one. Major figures like Descartes, Leibniz, Newton, and others developed an unprecedented secular theology whose debt to medieval and scholastic though shaped the trajectory of the scientific revolution. The book ends with Funkstein's influential analysis of the seventeenth century's "unprecedented fusion" of scientific and religious language. Featuring a new foreword, Theology and the Scientific imagination is a path breaking and classic work that remains a fundamental resource for historians and philosophers of science.